Towards Trust-Based Corporate Governance: Integration of Managerial Accountability and Organizational Integrity Beyond the Tariff Principle - Feliks Setia Wau; Posma Sariguna Johnson Kennedy (PT FORMOSA CENDEKIA GLOBAL, 2026)
Good corporate governance (GCG) has focused heavily on adherence to formal principles such as transparency, accountability, responsibility, independence, and fairness (TARIF). However, in practice, the application of these principles has not been fully effective in preventing managerial misconduct in various organizations. This article aims to examine the transformation of the GCG paradigm from a compliance-based governance approach to trustbased governance through the integration of managerial accountability and organizational integrity. The underlying phenomenon of this study is the continued prevalence of abuse of authority, moral hazard, and weak internalization of integrity values, despite the formal implementation of TARIF principles. This situation indicates a gap between procedural compliance and organizational ethical practices. This study uses a conceptual approach by reviewing the literature related to accountability, organizational integrity, and trust theory in governance. The results of the study indicate that trust-based governance can complement and strengthen TARIF principles, emphasizing interpersonal relationships, organizational culture, and the internalization of integrity values as a non-formal control mechanism. The integration of managerial accountability and organizational integrity enables the formation of a governance system that is not only procedurally compliant but also substantively ethical. The main contribution of this article is the development of a conceptual model of trust-based governance that goes beyond the traditional GCG approach. This model is expected to serve as a new framework for strengthening the effectiveness of corporate governance in the era of modern organizational complexity.